Assessment of Recovery From Geriatric Ankle Fracture Using the Life Space Mobility Assessment (LSA): A Pilot Study. Issue 4 (29th October 2018) - Ahearn, Briggs; Mueller, Claire; Boden, Stephanie; Mignemi, Danielle; Tenenbaum, Shay; Bariteau, Jason
Background: The Life Space Assessment (LSA) is a validated outcomes measure that aims to assess the level of mobility and physical functioning within one's own environment following a medical event. We sought to study the recovery of geriatric ankle fracture patients utilizing the LSA. We hypothesized that the LSA would provide improved assessment of these patients and help identify key differences in operative and nonoperatively treated patients. Methods: Prospective observational study of geriatric patients age 65 years and older with an ankle fracture with 1-year follow-up. Operative versus nonoperative intervention was determined by the attending physician on a patient-specific basis. The LSA, Short Form–36 (SF-36), and visual analog pain scale (VAPS) were administered at predetermined intervals postinjury and scores were analyzed for significance. Results: 20 patients were enrolled in this study. 11 underwent surgery whereas 9 were treated nonoperatively. Regardless of treatment, the preinjury LSA score was 86.7. This significantly dropped to 20.6 at 6 weeks and recovered to 73.6 at 12 months. In the operative cohort, the LSA scores preinjury were 91.4 and improved to 87.6 after 1 year. The nonoperative group recorded 80.9 preinjury and only improved to 59.5 at 1 year ( P = 0.007). There was no statistically significant difference when comparing the results of the SF-36 and VAPS to the LSA. Conclusion: The LSA was effective in assessing recovery in geriatric ankle fracture patients. A severe deficit in mobility was seen for the first 6 months of recovery regardless of treatment. Operative patients ultimately returned to their baseline LSA at 1 year while nonoperative patients did not. Outcomes from the VAS and SF-36 mirrored the LSA but were not found to be statistically significant. Level of Evidence: Level II.